Histone modifications: mechanisms, metabolic regulation and therapeutic targeting in cancer - Lingli Wang; Shiying Li; Xiaoyan Hu; Kui Ming Chan; Yang Meng; Junhong Han (Precision Clinical Medicine, 2026)
Abstract Histone post-translational modifications are central regulators of chromatin organization and genome function, acting independently of alterations in DNA sequence. This review comprehensively summarizes the multifaceted roles of major histone modifications including acetylation, methylation, ubiquitination, phosphorylation and emerging metabolism-linked acylations in governing critical DNA-templated processes such as replication, transcription, and the DNA damage response. We further discuss the concept of the nuclear metabolic microenvironment, in which local metabolite availability and enzyme activity directly influence the deposition of histone acylation marks and thereby connect metabolic state to chromatin regulation. We also examine how dysregulation of these pathways promotes tumor initiation and progression, facilitates immune evasion, and drives therapeutic resistance. On this basis, we evaluate current therapeutic strategies targeting histone-modifying machinery in cancer, including approved epigenetic drugs, agents in clinical development, biomarker-guided applications, resistance mechanisms, and combination approaches. We further distinguish direct pharmacological targeting of histone writers, erasers, and readers separately from indirect interventions against upstream kinases, metabolic pathways, or organelle-level metabolic remodeling. Together, these observations highlight the biological and translational importance of histone modifications in cancer and support continued development of mechanism-informed and biomarker-guided epigenetic therapies in precision oncology.